2009
DOI: 10.1590/s0100-204x2009000600011
|View full text |Cite
|
Sign up to set email alerts
|

Perdas fermentativas, composição química, estabilidade aeróbia e digestibilidade aparente de silagem de cana-de-açúcar com aditivos químico e microbiano

Abstract: O objetivo deste trabalho foi avaliar a influência da adição de cal virgem e Lactobacillus buchneri em perdas fermentativas, valor nutritivo, estabilidade aeróbia e digestibilidade aparente da silagem de cana-de-açúcar (Saccharum officinarum). O primeiro experimento avaliou perdas fermentativas, pH e temperatura, composição química e digestibilidade in vitro da matéria seca de silagens de cana-de-açúcar, com adição ou sem adição de cal ou de inoculante bacteriano (L. buchneri); o segundo avaliou o consumo de m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
1
17
0
7
Order By: Relevance
“…It is also possible that the ammonia produced from the urease did not act by inhibiting the yeasts, which, in turn, consumed sucrose, with a consequent loss of nutrients. Balieiro Neto et al (2009) found an average 28.0% NFC in sugarcane silages without additive or with 0.5% CaO. Thus, the use of 1% CaO or the association of CaO (0.5%) with urea (0.5%) in this study contributed favorably to the nutritive quality of the silage.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…It is also possible that the ammonia produced from the urease did not act by inhibiting the yeasts, which, in turn, consumed sucrose, with a consequent loss of nutrients. Balieiro Neto et al (2009) found an average 28.0% NFC in sugarcane silages without additive or with 0.5% CaO. Thus, the use of 1% CaO or the association of CaO (0.5%) with urea (0.5%) in this study contributed favorably to the nutritive quality of the silage.…”
mentioning
confidence: 52%
“…The results found in this study corroborate the reports of Santos et al (2009), in research with sugarcane silages without additives or with chemical additive (1% or 1.5% CaO, 1% or 1.5% CaCO 3 , and 1% gypsum). Balieiro Neto et al (2009) found the highest NDF levels in silages without additives, and the lowest in silages with 1% CaO or 1.5% CaCO 3 . Therefore, according to the results found in this study and those from the abovementioned literature, it can be inferred that among the studied additives, calcium oxide was the most efficient in reducing the fiber and improving the nutritive quality of sugarcane silage (MENDES et al, 2010).…”
mentioning
confidence: 93%
“…Segundo Huhtanen et al (2002), a utilização de aditivos é feita com o intuito de assegurar uma boa fermentação e minimizar as perdas durante a ensilagem, porém as alterações decorrentes do processo fermentativo influenciam o consumo. Balieiro Neto et al (2009) avaliaram o consumo de MS por ovinos Ile de France e reportaram consumo de 0,657 (1,60% do PV) e 0,720kg (1,61% do PV) para dietas à base de cana-de-açúcar in natura e silagem tratada com 0,5% de óxido de cálcio, respectivamente.…”
Section: Resultsunclassified
“…Entre os aditivos mais utilizados para esse fim, encontra-se a cal virgem (óxido de cálcio -CaO), a qual pode reduzir os constituintes da parede celular por hidrólise alcalina e contribuir para a preservação de nutrientes solúveis por inibir o desenvolvimento de leveduras que atuam sobre a massa ensilada, amenizando a perda de nutrientes durante a ensilagem e após a abertura do silo (Balieiro Neto et al, 2007;Amaral et al, 2009). Balieiro Neto et al (2009 observaram que ovinos alimentados com cana-de-açúcar in natura e silagem de cana-de-açúcar acrescida de cal virgem apresentaram consumo de matéria seca semelhante, sendo esses resultados superiores ao observado com utilização de aditivo microbiano (Lactobacillus buchneri).…”
unclassified
“…Research on ensilage in Brazil has progressed considerably following the frequent use of experimental silos (lab silos), including the widespread usage of PVC pipes (Ávila et al, 2010), plastic drums (Amaral et al, 2009), plastic buckets with a capacity of five liters (Balieiro Neto et al, 2009) or 20 liters (Pedroso et al, 2007), as well as other methods. The use of lab silos allows for measuring the quality and fermentation losses in the form of gases and effluents (Jobim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%